ANALISIS BIAYA DIFFERENSIAL DALAM MENERIMA ATAU MENOLAK PESANAN KHUSUS DI CV. ZAM ZAM COLLECTION JOMBANG - Lailatus Sa'adah (Fakultas Ekonomi Universitas KH. A. Wahab Hasbullah Tambakberas Jombang, 2019)
Differential costs are differences in costs or different costs in several alternative choices. Differential costs involve information that will come and differ between alternatives to be chosen and unique. Differential costs are always related to alternatives that are being considered for selection, Always relevant to alternative decision choices Better benefits Differential costs only cover different costs under certain conditions. If decision making is related to the utilization of production capacity, an understanding of the behavior of costs in relation to changes in the volume of activities is very important to be able to form differential costs that will be used as the basis for selecting alternative actions. The purpose of this study is to analyze differential costs in relation to decision making in accepting special orders. The analytical method used is descriptive quantitative method. The results of the study indicate that the company has been able to analyze differential costs in making decisions to receive special orders. companies should always apply differential cost analysis in order to be able to make informed decisions on available alternative options. Keywords: differential costs, special orders.